Nimble Approach: fast, adapting, calculating and ethically mindful approach to managing colorectal cancer screening programmes during a pandemic. Issue 1 (19th January 2022) - Baxter, Nancy N; Facey, Marcia; Ruco, Arlinda; Baker, Natalie A; Sorvari, Anne; Benmessaoud, Amina; Dube, Catherine; Rabeneck, Linda; Tinmouth, Jill
Abstract : Objective: To describe a conceptual framework that provides understanding of the challenges encountered and the adaptive approaches taken by organised colorectal cancer (CRC) screening programmes during the initial phase of the COVID-19 pandemic. Design: This was a qualitative case study of international CRC screening programmes. Semi-structured interviews were conducted with programme managers/leaders and programme experts, researchers and clinical leaders of large, population-based screening programmes. Data analysis, using elements of grounded theory, as well as cross-cases analysis was conducted by two experienced qualitative researchers. Results: 19 participants were interviewed from seven programmes in North America, Europe and Australasia. A conceptual framework ('Nimble Approach') was the key outcome of the analysis. Four concepts constitute this approach to managing CRC screening programmes during COVID-19: Fast (meeting the need to make decisions and communicate quickly), Adapting (flexibly and creatively managing testing/colonoscopy capacity, access and backlogs), Calculating (modelling and actively monitoring programmes to inform decision-making and support programme quality) and Ethically Mindful (considering ethical conundrums emerging from programme responses). Highly integrated programmes, those with highly integrated communication networks, and that managed greater portions of the screening process seemed best positioned to respond to the crisis. Conclusions: The Nimble Approach has potentially broad applications; it can be deployed to effectively respond to programme-specific challenges or manage CRC programmes during future pandemics, other health crises or emergencies.